Investigating lens elasticity and its correlation with refractive errors and biometric parameters across age groups using ultrasonic elastography shear wave - Bahari, Norafida; Abdul Rahim, Ezamin; Md Salleh, Rafidah; Qader, Alaa Hussein; Mohamad Zain, Muhsonat (Ajmedtech, 2024)
The lens in human eyes possesses elastic properties that facilitate shape change to focus light onto the retina, with ultrasound elastography shear wave being a common imaging technique to assess tissue elasticity. This study aimed to determine the correlation between lens elasticity and various factors across different age ranges, including refractive error and biometric properties (axial length and lens thickness). The study included responses from 84 individuals aged 19 to 65, with eligibility determinedthrough tests assessing refractive errors and visual acuity. Axial length and lens thickness were measured after selecting the best eye for testing, followed by scanning with ultrasound elastography using shear wave technology. The data analysis revealed a significant correlation between participants'age and lens elasticity (r = 0.83, P = 0.00), an insignificant correlation between elasticity and refractive error (r = 0.247), weak correlations with axial length (r = 0.006), lens thickness (r = 0.27, P = 0.14), and a negative correlation between axial length and lens thickness (r = 0.233, P = 0.033). The results indicated that the alterations do not appreciably influence lens elasticity changes with age, but the variations in refractive error or ocular morphology.